Identifying stakeholders and analyzing their concerns about African swine fever control in wild boar - Janine Miesch; Jana Schulz; Barbara Thür; Katja Schulz; Annika Frahsa; Salome Dürr (Frontiers in Veterinary Science)
African swine fever (ASF) is approaching Switzerland as it continues to spread across Europe. This viral disease affects porcine species, leading to severe economic losses when reaching the domestic pig sector. Controlling ASF in wild boar populations is complex and requires coordination among diverse stakeholders with varying roles and interests. We used a participatory approach in data generation (including desk research, qualitative interviews, focus group discussions, and workshops) and applied reflexive thematic analysis to systematically identify relevant actors and assess their concerns, guided by the Mendelow Power-Interest Grid for stakeholder mapping. Results reveal a broad spectrum of stakeholders, including federal and cantonal-level authorities, the private industry sector, non-governmental organizations (NGOs) and private individuals, as well as academic and diagnostic institutions. Stakeholder mapping underscores the central role of federal and cantonal authorities in ASF control and demonstrates the hunting sector’s dual position as both being impacted by and being actively involved in control efforts. Stakeholders’ concerns fall into five key areas: economic risk, material shortages, legal frameworks and bureaucratic obstacles, challenges in communication and coordination, and animal welfare and environmental issues. Findings emphasize the need for improved governance, clearer guidelines, and stronger coordination among federal and cantonal authorities. The research demonstrates the value of participatory approaches for disease management by enhancing collaboration, identifying critical gaps, and strengthening preparedness and response efforts, on the example of ASF in Switzerland.